Prevalence, Clinical Presentation, and Factors Associated With Diabetic Foot Ulcer in Two Regional Hospitals in Cameroon. (March 2018) - Tindong, Maxime; Palle, John N.; Nebongo, Daniel; Aminde, Leopold Ndemnge; Mboue-Djieka, Yannick; Mbarga, Nicole T. Fouda; Dehayem, Mesmin Y.; Choukem, Siméon-Pierre
This study aimed to determine the prevalence of diabetic foot ulcer and high risk for ulceration, describe the clinical presentation, and identify factors associated with diabetic foot ulcer in the Southwest regional hospitals of Cameroon. In this cross-sectional study, data were collected using a structured questionnaire administered to consecutive patients with diabetes. Findings from detailed foot examination were recorded. Diabetic foot ulcer was diagnosed according to the International Working Group on Diabetic Foot (IWGDF) definition. Data were analyzed with Stata IC version 12. Of the 203 participants included, 63.1% were females. Age ranged from 26 to 96 years. The median duration of diabetes was 4.0 years (interquartile range 1.0-8.0 years). The prevalence of diabetic foot ulcer was 11.8% (24), of whom 29.2% (7) had high grade (grades 2 to 4), and most of the ulcers 58.3% (14) were located at the plantar region. The prevalence of high risk for ulceration was 21.8% (39). Loss of protective sensation (OR = 3.73, 95% CI = 1.43-9.71; P = .007), and peripheral arterial disease (OR = 3.48, 95% CI = 1.14-10.56; P = .028) were independently associated with diabetic foot. Diabetic foot ulcer is a common complication among patients with diabetes attending these regional hospitals. Loss of protective sensation, and peripheral arterial disease increase the odds of having diabetic foot ulcer, and we suggest them as the main target of interest for prevention.